2000
DOI: 10.1046/j.1523-1755.2000.00149.x
|View full text |Cite
|
Sign up to set email alerts
|

Podocyte cell cycle regulation and proliferation in collapsing glomerulopathies

Abstract: The loss of p27 and p57 leading to expression of cyclin A may account for the activation of podocyte proliferation in CG. Furthermore, the loss of cyclin D1 from histologically normal glomeruli suggests a possible role of cyclin D1 in mediating the dysregulation of the podocyte cell cycle in CG. These novel findings offer insight into the molecular regulation of mature podocyte differentiation. Podocyte proliferation in CG provides evidence in support of a previously underestimated plasticity of mature podocyt… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

8
137
0

Year Published

2002
2002
2012
2012

Publication Types

Select...
10

Relationship

1
9

Authors

Journals

citations
Cited by 172 publications
(145 citation statements)
references
References 22 publications
(5 reference statements)
8
137
0
Order By: Relevance
“…Many studies have suggested that epithelial hyperplasia in various glomerular diseases is characterized by cells that stain negatively for podocyte markers (eg synaptopodin and PHM-5) and CKIs, stain positively for cytokeratin, and occasionally stain positively for CDK2, Ki-67 and cyclins (E, A, B1). 7,25,[36][37][38] We now provide evidence of PCNA, c-Myc and E2F1 overexpression in these lesions against a background of absent p27 kip1 and p57 kip2 expression in IgAN. Novel findings included a weak to moderate expression of p21 waf1 and p16 ink4a in these cellular lesions, in addition to the colocalization of p21 waf1 with PCNA in these epithelial lesions.…”
Section: Discussionmentioning
confidence: 53%
“…Many studies have suggested that epithelial hyperplasia in various glomerular diseases is characterized by cells that stain negatively for podocyte markers (eg synaptopodin and PHM-5) and CKIs, stain positively for cytokeratin, and occasionally stain positively for CDK2, Ki-67 and cyclins (E, A, B1). 7,25,[36][37][38] We now provide evidence of PCNA, c-Myc and E2F1 overexpression in these lesions against a background of absent p27 kip1 and p57 kip2 expression in IgAN. Novel findings included a weak to moderate expression of p21 waf1 and p16 ink4a in these cellular lesions, in addition to the colocalization of p21 waf1 with PCNA in these epithelial lesions.…”
Section: Discussionmentioning
confidence: 53%
“…However, podocytes in adults are known to have a limited potential for cell proliferation (22,23). In collapsing FSGS, dysregulated podocytes lose the expression of specific markers and seem to proliferate in a manner reminiscent of localized benign neoplastic growth (24). In a transgenic mouse model, genetic reduction of the expression of WT-1, a transcription factor expressed exclusively in podocytes in the kidneys of adult mice, was sufficient to induce cell proliferation in dysregulated podocytes and resulted in the formation of cellular crescents (25).…”
Section: Discussionmentioning
confidence: 99%
“…In either case, these results strongly suggest that a link exists between the regulation of cytoskeletal function and nephrin expression. Expression of the transcription factor WT-1, a podocyte-lineage marker, has been previously shown to be downregulated in some nonfamilial forms of collapsing and noncollapsing FSGS, thereby suggesting a reversion of the podocyte to a more immature/proliferating phenotype (4,41,42). However, we now show that WT-1 mRNA levels and immunofluorescence of synaptopodin (data not shown), another podocytespecific marker, were not significantly different between the three groups of mice, thereby suggesting that despite the reduced nephrin expression, these cells maintained a somewhat differentiated phenotype.…”
Section: Discussionmentioning
confidence: 99%